A scheme of arrangements and a proposal of composition in the law of bankruptcy: an analytical discussion / Madihah Zainal Abidin - Zainal Abidin, Madihah (Faculty of Law, 1982)
The availability of credit is a fundamental requirement for the satisfactory functioning of any modern society. But closely linked to this need for credit, is the need for a law of bankruptcy, to make provisions for that state of insolvency which can unfortunately occur a consequence of credit. Therein of course, lies the element of risk inherent in the granting of credit for the creditor is dependant upon this debtor’s being both able and willing to settle the account on the date agreed, and may, moreover proceed to arrange his own affairs on the assumption that he will receive that payment when It falls due. Consequently, the inability or refusal of the debtor to honour his obligation may furnish embarassment also to the creditor who in his turn may become unable to meet his own obligation owed to others. It may be observed, at this point, that a failure to settle a debt promptly maybe due either to the debtor’s lack of the means to pay at that moment or to his deliberate refusal to pay albeit that he possesses the means so to do. In either case, his failure to pay can entail very serious consequences for those who have extended credit to him, and it is thus essential that the law should provide an adequate range of remedies which are capable of affording the creditor as high a degree of protection as possible.